La sémantique des noms : taxinomie djihadiste et imaginaire médiéval - Enki Baptiste (Frontière·s)
This paper analyses Islamic State’s medievalism through the French and English editions of the magazines published by the terrorist organization. It focuses on the names of press organs or battalions, but also on those used by jihadist militants as kunya. Jihadist materials, by linking to mythologized past of the call of the Prophet Muḥammad and the first caliphs, exude a medievalist universe imbued with a cyclical reading of the history of conquest, in which jihadists see themselves as the heirs of the Prophet’s companions. In the context of the Syrian civil war, the reinvestment of apocalyptic literature allows the terrorist organization’s state project to be supported, despite its pitfalls. Ultimately, unravelling the jihadist discourses means foremost exploring the semantics of names, in which powerful, shared references to a grand narrative emerge. Within this narrative, the warriors of the Prophet and those of the jihadist caliphate merge.